P5 Development Of Independence In Caring For Oneself Through Practice-Based Learning - Hadi Suryanto (Hanoman Journal: Physical Education and Sport, 2022)
Teachers are designers and an important act of this profession is to structure learning experiences to meet specific goals. Activities were carried out in Kediri Regency for schools participating in the driving school program, totaling 6 schools and 18 teachers involved. Next, research subjects were selected from 2 schools and 2 teachers who were implementing a project to strengthen the profile of Pancasila students with elements of self-care independence. Two research questions guided this study: (1) What are teachers' experiences implementing practice-based learning? (2) How can the teacher's role develop throughout the entire learning path? Qualitative data were collected from workshops, observations of self-care independence sessions in grade 10, and interviews with teachers and students. The research results obtained by teachers emerged as a conceptual shift, abandoning the role of organizer, and instead pursuing the role of a close, curious, and questioning teacher, utilizing different teaching styles to meet students' needs. The turning point for teachers emerged as a conceptual shift, abandoning the role of organizer, and instead pursuing the role of close, inquisitive, and questioning teacher, utilizing different teaching styles to meet students' needs.